Pro-apoptotic effects of Kangfuxin on human stomach cancer cells and its underlying mechanism - Ma, Xiuying (Oncol Lett, 2018)
Kangfuxin (KFX) is an oral liquid derived from Periplaneta americana, with complex components. KFX has been demonstrated to exhibit anticancer activity in a variety of different types of tumor, including gastric cancer; however, its underlying molecular mechanism remains unclear. The present study was designed to investigate the pro-apoptotic effects of KFX on SGC-7901 cells, in order to provide a theoretical basis for clinical application. In order to clarify the pro-apoptotic effects of KFX on SGC-7901 cells, MTT analysis was conducted. To evaluate the anticancer effect of KFX, peroxisome proliferator-activated receptor (PPAR)-γ was analyzed by reverse transcription-polymerase chain reaction. Western blot analysis was used to determine the effects of KFX on the expression of cleaved caspase-3, phosphorylated extracellular signal-regulated kinase (p-ERK), ERK, tumor protein p53 (p53), B-cell lymphoma 2 (Bcl-2), Bcl-2 associated X, interleukin (IL)-6 and IL-1β. In addition, terminal deoxynucleotidyl-transferase-mediated dUTP nick-end labeling (TUNEL) analysis was used to detect apoptosis in SGC-7901 cells. It was revealed that PPAR-γ was increased in SGC-7901 cells following treatment with KFX, shown by an increase in mRNA expression. Furthermore, western blot analysis identified that KFX treatment groups exhibited markedly inhibited levels of Bcl-2, IL-6, IL-1β and p-ERK, and induced p53 protein expression. Additionally, TUNEL and MTT assays demonstrated that treatment with KFX may induce SGC-7901 cell apoptosis and inhibit proliferation. In conclusion, to the best of our knowledge, the results of the present study demonstrated for the first time that KFX may induce SGC-7901 cell apoptosis and inhibit its proliferation, and this may be primarily attributed to its role in mitogen-activated protein kinase/extracellular-signal-regulated kinase kinase/ERK signaling pathway inhibition.